The c-Myc/miR17-92/PTEN Axis Tunes PI3K Activity to Control Expression of Recombination Activating Genes in Early B Cell Development - Benhamou, David; Labi, Verena; Getahun, Andrew; Benchetrit, Eli; Dowery, Reem; Rajewsky, Klaus; Cambier, John C.; Melamed, Doron (Frontiers in Immunology, 2018)
Appropriate PI3K signals generated by the antigen receptor are essential to promote B cell development. Regulation of recombination activating gene (RAG)-1 and RAG-2 expression is one key process that is mediated by PI3K to ensure developmental progression and selection. When PI3K signals are too high or too low, expression of RAGs does not turn off and B cell development is impaired or blocked. Yet, the mechanism which tunes PI3K activity to control RAG expression during B cell development in the bone marrow is unknown. Recently we showed that a c-Myc/miR17-92/PTEN axis regulates PI3K activity for positive and negative selection of immature B cells. Here we show that the c-Myc/miR17-92/PTEN axis tunes PI3K activity to control the expression of RAGs in proB cells. Using different genetically engineered mouse models we show that impaired function of the c-Myc/miR17-92/PTEN axis alters the PI3K/Akt/Foxo1 pathway to result in dis-regulated expression of RAG and a block in B cell development. Using 38c-13 B lymphoma cells, where RAGs are constitutively expressed, we show that this regulatory effect is mediated post-translationally through Foxo1.